2009
DOI: 10.1126/science.1178712
|View full text |Cite
|
Sign up to set email alerts
|

Planarian Hh Signaling Regulates Regeneration Polarity and Links Hh Pathway Evolution to Cilia

Abstract: The Hedgehog (Hh) signaling pathway plays multiple essential roles during metazoan development, homeostasis, and disease. Although core protein components are highly conserved, the variations in Hh signal transduction mechanisms exhibited by existing model systems (Drosophila, fish, and mammals) are difficult to understand. We characterize the Hh pathway in planarians. Hh signaling is essential for establishing the Anterior/Posterior axis during regeneration by modulating wnt expression. Moreover, RNAi methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
259
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(286 citation statements)
references
References 39 publications
25
259
1
1
Order By: Relevance
“…S9 in the supplementary material) and this decrease was not influenced by anteriorization. In addition, Dj-cateninB(RNAi) had little effect on the expression of Djwnt1/P-1 at day 1, as previously described (Petersen and Reddien, 2009;Rink et al, 2009). This result showed that, at least in the first phase, Djwnt1/P-1 is expressed independently of the -catenin pathway, in contrast to the other Wnt and posterior genes.…”
Section: Djwnt1/p-1 Signal Is Upstream Of the Posterior Wnt Genesmentioning
confidence: 81%
See 1 more Smart Citation
“…S9 in the supplementary material) and this decrease was not influenced by anteriorization. In addition, Dj-cateninB(RNAi) had little effect on the expression of Djwnt1/P-1 at day 1, as previously described (Petersen and Reddien, 2009;Rink et al, 2009). This result showed that, at least in the first phase, Djwnt1/P-1 is expressed independently of the -catenin pathway, in contrast to the other Wnt and posterior genes.…”
Section: Djwnt1/p-1 Signal Is Upstream Of the Posterior Wnt Genesmentioning
confidence: 81%
“…, however, shows a tail formation defect and inappropriate midline patterning after posterior amputation (Gurley et al, 2010). Furthermore, it has been shown that Hedgehog (Hh) signaling is upstream of Wnt/-catenin signaling and is involved in the establishment of anterior-posterior (AP) polarity (Rink et al, 2009;Yazawa et al, 2009). These studies clearly indicate that signaling molecules plays a crucial role, not only in regeneration, but also in cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…nou darake (ndk), ndl-4, sFRP-1, notum and prep were selected as anterior PCGs (Cebrià et al, 2002;Gurley et al, 2008;Reddien, 2008, 2011;Rink et al, 2009;Felix and Aboobaker, 2010); wnt2 and ndl-3 were selected as prepharyngeal PCGs (Petersen and Reddien, 2008;Rink et al, 2009); and wntless, wntP-2, frizzled-4 ( fz-4), axinB and wnt1 were selected as posterior PCGs (Gurley et al, 2008;Petersen and Reddien, 2008;Adell et al, 2009;Iglesias et al, 2011). We used a highly parallel microfluidic qRT-PCR platform (Fluidigm) to assess gene expression in wild-type, control, β-catenin-1 and teashirt RNAi animals (supplementary material Fig.…”
Section: Teashirt and Other Wnt-dependent Processesmentioning
confidence: 99%
“…81 In planaria worms, a reduction in signal transduction proteins coded by cos2/kif27/kif7, fused, or iguana does not result in detectable Hh signaling defects but appears to be essential for planarian ciliogenesis. 81 Interestingly, the protein KIF27 was recently shown to physically interact with Fused (STK36), a critical protein in the construction of the central pair apparatus of motile 9þ2 cilia in mice. 106 Taken together, these earlier reports, plus our findings of hydrocephalus and other lesions that are characteristic of ciliary dyskinesia, support an interactive role for both Kif27 and Stk36 in ciliogenesis.…”
mentioning
confidence: 99%